[PP.18.21] MUSCLE SYMPATHETIC NERVE ACTIVITY IS ASSOCIATED WITH ELEMENTS OF THE PLASMA LIPIDOMIC PROFILE IN YOUNG ASIAN ADULTS AT LOWER LEVELS OF OBESITY. (September 2017) - Eikelis, N.; Lambert, E.; Phillips, S.; Sari, C.; Weir, J.; Huynh, K.; Dixon, J.; Schlaich, M.P.; Meikle, P.; Lambert, G.
Abstract : Objective: Asian subjects are at increased cardio-metabolic risk at comparatively lower BMI compared with Caucasians. Sympathetic nervous system activation and dyslipidaemia, both characteristics of increased adiposity, appear to be related. We therefore analysed the association of muscle sympathetic nerve activity (MSNA) with the plasma lipidomic profile in young Asian and Caucasian subjects. Design and method: Blood samples were collected from 101 participants of either Asian or Caucasian background, aged 18–30, BMI 28.1 ± 5.9 kg/m 2 . Lipids were extracted from plasma and analysed using electrospray ionization-tandem mass spectrometry. MSNA was quantified using microneurography. The association of MSNA and obesity with lipid species was examined using linear regression analysis. Results: Despite Caucasians having greater BMI and waist circumference there was no difference in blood pressure or MSNA between groups. The plasma concentration of total dihydroceramide, ceramide, GM3 ganglioside, lysoalkylphosphatidylcholine, alkenylphosphatidylethanolamine and lysophosphatidylinositol were elevated in the Asians compared to Caucasians. After adjustment for confounders, di- and triacylglycerols, cholesterol esters, phosphatidylinositols, phosphatidylethanolamines and phosphatidylglycerols bore significant association with MSNA but only in the Asians. These associations remained significant after further adjustment for the participants' degree of insulin resistance and appeared not to be related to difference in diet macronutrient content between groups. Conclusions: The lipidomic profile differs between Asian and Caucasian subjects. There exists a strong relationship between certain lipid species and MSNA. Despite having a lower BMI the association is stronger in the Asians. This study adds further support of the interaction between circulating lipids and central sympathetic outflow. Whether the stronger association between the lipid profile and sympathetic activation underpins the apparent greater risk posed by increased adiposity in Asians merits further attention.